Efeitos do treinamento f??sico aer??bio na inflama????o pulmonar al??rgica cr??nica em camundongos: papel da sinaliza????o purin??rgica - Greiffo, Fl??via Regina (2015)
In the last years, a growing number of studies have demonstrated that the aerobic physical training (APT), performed in the proper intensity, duration and frequency, display several benefits to asthmatic patients, including improvement in quality of life, reduction in the levels of anxiety and depression, improvements in minute ventilation, reduction in the number of crisis, reduction in the levels of exhaled nitric oxide, beyond reduced daily needing of corticosteroids. More recently, was demonstrated for the first time that APT presents a direct anti-inflammatory effect on the airways of asthmatic patient, since that APT reduced the number of eosinophils in the induced sputum of these patients. However, several questions and hypothesis were raised up about the possible mechanism involved in these anti-inflammatory effects of APT for asthma. In this way, a growing number of experimental studies using models of asthma have been published, revealing possible mechanism involved of action APT for asthma. On the other hand, until this moment no study evaluated the effects of APT on the via of purinergic receptors, a family of receptors that present a central role in the physiopathology of asthma. Therefore, the present study aim is to evaluate if the anti-inflammatory effects of APT for asthma is mediate, at least partially, by the inhibition of expression of purinergic receptor P2X7, as well as the extracellular adenosine triphosphate (ATP). Thus, using 40 C57Bl/6 mice, divided in 4 experimental groups (Control, n = 10), (Exercise, n = 10), (Asthma, n = 10) and (Asthma + Exercise, n = 10). The experimental model of asthma (chronic pulmonary allergic inflammation) was induced through the intra-peritoneal injection of ovalbumin solution on days 0, 14, 21 and 42 followed by inhalation of 1%, 3% and 5% ovalbumin, 3x/week, and beginning on 21st day until the 53rd day of experimental protocol. To evaluate the therapeutic effects of APT on the inflammation and on the via of purinergic receptors, the low intensity APT was performed 5x/week, 60 min/session, begining on 27th day of experimental protocol until the 53rd day, when the airways inflammation is already established. Twenty-four hours after the last inhalation and training session, mice were anesthetized, tracheotomized, canuled and the bronchoalveolar lavage was collected and analyzed for the ATP levels and also the total number of cells as well as the differential number of cells. The analysis of hyperresponsiveness was performed. The histological analysis was performed to evaluate and quantify the number of lymphocytes and eosinophils in the airways wall, and also the airway remodeling. The expression of purinergic receptor P2X7 in the lung tissue homogenate was performed using western blotting and also the immunohistochemistry technique.